Antimalarial potential, LC–MS secondary metabolite profiling and computational studies of Zingiber officinale - Faloye K.O.; Tripathi M.K.; Adesida S.A.; Oguntimehin S.A.; Oyetunde Y.M.; Adewole A.H.; Ogunlowo I.I.; Idowu E.A.; Olayemi U.I.; Dosumu O.D. (My University, 2025)
Malaria is among the top-ranked parasitic diseases that pose a threat to the existence of the human race. This study evaluated the antimalarial effect of the rhizome of Zingiber officinale in infected mice, performed secondary metabolite profiling and detailed computational antimalarial evaluation through molecular docking, molecular dynamics (MD) simulation and density functional theory methods. The antimalarial potential of Z. officinale was performed using the in vivo chemosuppressive model; secondary metabolite profiling was carried out using liquid chromatography–mass spectrometry (LC–MS). Molecular docking was performed with Autodock Vina while the MD simulation was performed with Schrodinger desmond suite for 100 ns and DFT calculations with B3LYP (6-31G) basis set. The extract showed 64% parasitaemia suppression, with a dose-dependent increase in activity up to 200 mg/kg. The chemical profiling of the extract tentatively identified eight phytochemicals. The molecular docking studies with plasmepsin II and Plasmodium falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) identified gingerenone A as the hit molecule, and MMGBSA values corroborate the binding energies obtained. The electronic parameters of gingerenone A revealed its significant antimalarial potential. The antimalarial activity elicited by the extract of Z. officinale and the bioactive chemical constituent supports its usage in ethnomedicine. Communicated by Ramaswamy H. Sarma. © 2023 Informa UK Limited, trading as Taylor & Francis Group.